2019
DOI: 10.1111/pce.13526
|View full text |Cite
|
Sign up to set email alerts
|

Stress priming, memory, and signalling in plants

Abstract: Plants need to cope with changing environmental conditions, be it variable light or temperature, different availability of water or nutrients, or attack by pathogens or insects. Some of these changing conditions can become stressful and require strong countermeasures to ensure plant survival. Plants have evolved numerous distinct sensing and signalling mechanisms to perceive and respond appropriately to a variety of stresses.Because of the unpredictable nature of numerous stresses, resource-saving stress respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
144
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 219 publications
(168 citation statements)
references
References 106 publications
1
144
0
Order By: Relevance
“…As immovable organisms, plants need to cope with various environmental changes, including nutrient starvation, salt, drought, and heat stresses Shen et al, 2014;Qi et al, 2018;Hilker and Schmülling, 2019). To respond appropriately to these stresses, plants have evolved various distinct signaling and regulatory mechanisms (Hilker and Schmülling, 2019). It has been shown that autophagy is involved in removing damaged proteins and cellular components produced in response to environmental stresses (Wang et al, 2018b).…”
Section: Autophagy In the Plant's Response To Abiotic Stressmentioning
confidence: 99%
“…As immovable organisms, plants need to cope with various environmental changes, including nutrient starvation, salt, drought, and heat stresses Shen et al, 2014;Qi et al, 2018;Hilker and Schmülling, 2019). To respond appropriately to these stresses, plants have evolved various distinct signaling and regulatory mechanisms (Hilker and Schmülling, 2019). It has been shown that autophagy is involved in removing damaged proteins and cellular components produced in response to environmental stresses (Wang et al, 2018b).…”
Section: Autophagy In the Plant's Response To Abiotic Stressmentioning
confidence: 99%
“…In Ca 2+ signaling, Ca 2+ flux across membranes is promoted through the activity of several families of Ca 2+ -permeable channels, such as CNGCs. Plant cytoplasmic Ca 2+ is sensed by different Ca 2+ sensor proteins (e.g., CaMs, CMLs, CBLs, CDPKs), which further induce expression of downstream genes (e.g., transcription factors, NADPH oxidases genes) and mediate responses to abiotic and biotic stresses through reactive oxygen species (ROS) and/or nitrogen monoxide (NO) production [67,68]. CDPKs are involved not only in Ca 2+ -and ROS-mediated initiation of stress signaling, but also in hormone-regulated systemic signal propagation during pathogen infection [68,69].…”
Section: Regulation Of Genes In Ca 2+ -Dependent and Mapk Signal Pathmentioning
confidence: 99%
“…Plant cytoplasmic Ca 2+ is sensed by different Ca 2+ sensor proteins (e.g., CaMs, CMLs, CBLs, CDPKs), which further induce expression of downstream genes (e.g., transcription factors, NADPH oxidases genes) and mediate responses to abiotic and biotic stresses through reactive oxygen species (ROS) and/or nitrogen monoxide (NO) production [67,68]. CDPKs are involved not only in Ca 2+ -and ROS-mediated initiation of stress signaling, but also in hormone-regulated systemic signal propagation during pathogen infection [68,69]. On the other hand, the MAPK cascade generally has three components, a MAPK, a MAPKK (MAPK kinase) and a MAPKKK (MAPKK kinase), which play essential roles in plant growth and development as well as responses to abiotic and biotic stresses [67,68].…”
Section: Regulation Of Genes In Ca 2+ -Dependent and Mapk Signal Pathmentioning
confidence: 99%
See 1 more Smart Citation
“…Upon pre-exposure to abiotic stress, plants are able to establish a defense priming with a fast and/or strong activation of defense responses, including phytohormones, against subsequent challenges from microbes, insects, or other biotic stresses (Mauch-Mani et al, 2017;Hilker and Schmülling, 2019). Previous studies have shown that because of strong oxidative stress, pre-exposure to O 3 can prime tomato leaves for an enhanced defense against subsequent herbivorous insect infestation by upregulating the expression of salicylic acid (SA)-dependent defensive gene pathogenesis-related protein and increasing the emission of jasmonic acid (JA)-mediated monoterpene volatiles by tomato plants to decrease the population abundance and feeding fitness of B. tabaci (Cui et al, 2012;Cui et al, 2014).…”
Section: Introductionmentioning
confidence: 99%